Fabrication of Long and Smooth Tungsten Probes for Nano-manipulation - Wang, Xiangning; Liu, Xiaojun; Zhao, Hao; Chang, Ming; Chen, Liangzhou (Elektronika ir Elektrotechnika, 2015)
Long and smooth tungsten probe is useful for nano-manipulation. In this paper, an ameliorated straightforward dynamic electrochemical etching method and process for long and smooth tungsten probe fabrication have been developed. The relationships between the apex diameter and the aspect ratio of the probe and the fabrication process parameters have been systematically investigated. It’s noticed that by process parameter control, the apex size and the shape of the ultra-sharp probe are controllable and reproducible, and the diameter of the probe can be consistently less than 200 nm while its aspect ratio larger than 8 with the same gradient. To get high efficient yield, the consuming time is also researched. Through practical testing and applications as end-effectors in nano-manipulation, the usability and good quality of the fabricated probes have been verified because of their easy availability, high hardness and wear resistance. DOI: http://dx.doi.org/10.5755/j01.eee.21.4.12775